2014
DOI: 10.1186/1476-069x-13-70
|View full text |Cite
|
Sign up to set email alerts
|

Exposure characteristics of familial cases of lung injury associated with the use of humidifier disinfectants

Abstract: BackgroundThis study describes 17 families with 38 lung injury patients (14 males, 24 females; 22 preschool-age children less than six years of age and 16 individuals of 13–50 years) who used disinfectant added to humidifiers in the home.MethodsClinical examination and humidifier disinfectant-use histories were taken, and a thorough home investigation was performed to assess exposure to humidifier disinfectant.ResultsNine of the patients (three pregnant females, six preschool-age children) died soon after they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 12 publications
(16 reference statements)
0
25
0
Order By: Relevance
“…Polyhexamethylene guanidine phosphate (PHMG-p) was used as a major component of humidifier disinfectants to clean humidifiers and remove microbial growth in South Korea. However, epidemiological and toxicological studies have revealed that PMHG-p induces pulmonary inflammation and fibrosis (Park et al, 2014;Song et al, 2014). Exposure to PHMG-p via inhalation has been previously found to cause the release of cytokines, the infiltration of inflammatory cells, and the formation of fibroblast foci in rodents (Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Polyhexamethylene guanidine phosphate (PHMG-p) was used as a major component of humidifier disinfectants to clean humidifiers and remove microbial growth in South Korea. However, epidemiological and toxicological studies have revealed that PMHG-p induces pulmonary inflammation and fibrosis (Park et al, 2014;Song et al, 2014). Exposure to PHMG-p via inhalation has been previously found to cause the release of cytokines, the infiltration of inflammatory cells, and the formation of fibroblast foci in rodents (Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In animal studies performed by the KCDC, inhalation of PHMG and PGH revealed histopathological readings identical to those of patients with HDLI in November 2011 [10, 15, 16]. However, a mixture of CMIT/MIT has not been proven in a laboratory experiment to be directly related to HDLI despite the presence of patients diagnosed with HDLI, unlike PHMG and PGH.…”
Section: Introductionmentioning
confidence: 99%
“…Each group was also stratified into four groups: 6 years old or younger, between 6 and 18 years of age, pregnant women, and 18 years of age or older (excluding pregnant women). These strata were identified for future epidemiological analyses to test whether the level of susceptibility or sensitivity to disinfectants may be substantially different among these groups (Lebowitz, 1995;Park et al, 2014). In addition, the diverse types of disinfectants used were categorized into guanidine (PGH and PHMG) and non-guanidine group chemicals (CMIT and MIT) because the toxicity between the two types may be different.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al. () conducted thorough home investigations of 17 families that had at least two cases of lung disease that were presumed associated with the use of humidifier disinfectant and found no other home or occupational exposures that could explain the lung disease. These lung disease patients included a number of pregnant women, infants, and preschoolers, who may be particularly vulnerable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation